PENGARUH PEMBELAJARAN POE (PREDICT OBSERVE EXPLAIN) MELALUI METODE EKSPERIMEN DAN DEMONSTRASI TERHADAP HASIL BELAJAR DITINJAU DARI KEMAMPUAN AWAL DAN KETERAMPILAN GENERIK SAINS SISWA - Siti Muthmainah; Mohammad Masykuri; Baskoro Adi Prayitno (Magister Pendidikan Sains Universitas Sebelas Maret, 2019)
The aims of this reasearch are to find out the influence of POE model through experiment and demonstration methods viewed by prior knowledge and generic science skill and the interaction of them to students’ cognitive, afective, and phsycomotor learning achievements on environment pollution subject. The population of this reseach was all students of the seventh grade of MTs PPMI Assalam Sukoharjo. The sample of this reseach was determined by using cluster random sampling and the result got two classes. Experiment class I (7C) used POE model with experiment method and experiment class II used POE model with demonstration method. Data collected technique used test to get students’ cognitive achievement, while observation sheets were used to get students’ affective and phsycomotor acievements, and test sheets were used to get students’ prior knowledge and generic science skill. Hypothesis was analyzed used ANAVA. The results of the research were as follow: There was influence of prior knowledge and generic science skill to the student cognitive achievement and also there was interaction between the POE model through experiment and demonstration methods, prior knowledge, and generic science skill to the students’ cognitive achievement.